Ordering the doctors: new code of ethics - Nayar, K.R. (2002)
The new regulation for ethical medical practice, prompted no doubt by public concern about medical misconduct, is unfortunately a vague and weak regulatory instrument. How effective will it be in monitoring unethical practices? - Reproduced.
Keywords: Medical ethics